Teachers' self and the lifelong learning transitions through networked learning experiences - Raffaghelli, Juliana E. (Proceedings of the International Conference on Networked Learning, 2012)
The preparation of quality teachers, as important factor affecting student performance (Rivkin, Hanushek, Kain, 2005), gains attention within the ET 2020 strategy (European Commission, 2010), highlighting the complex role of teachers as mediators/facilitators within a changing educational system that aims to respond to a rapidly evolving world. Appropriated teachers' education should mix activities that promote formal and non-formal/informal learning, through social interaction, as part of a context of professional development (Villegas-Reimers, 2003; OCDE-TALIS, 2010; Margiotta, 2007); this has been proven to be a key issue of teachers' continuing commitment with innovations and quality of learning at school (Barber & Moursher, 2007; Ellerani & Paricchi, 2010). To this regard, the Web is creating new opportunities for learning, where teachers education and continuing training could also take place effectively (Twining, 2011; Raffaghelli & Tosato, 2011). As emphasized by the networked learning perspective, interconnectedness between resources, peers and trainers, allow effective learning. This definition is coherent with the new perspectives on teachers' professional development (Zenios et al, 2004; Hanraets et al. 2011) . In line with this, the present paper studies how teachers' conceptions on pedagogical practices changed through the participation to networked learning experiences within the frame of a transnational project (COMENIUS LLP P.I.N.O.K.I.O project: "Pupils for Innovation as Key for Intercultural and Social Inclusion"); to do this, teachers' narratives about exploration and implementation of the project's method within professional practice were analyzed. The conclusions emphasize the links between learning biographies and teachers' discourses within networked learning experiences. These elements could be considered as increasingly indistinguishable in a lifelong learning perspective of the teaching profession, since teachers connect their own identities with the results of meaning making processes in the several, interconnected learning spaces on the Web; by adopting technological tools and spaces, they connect the several learning cultures, resources and pedagogical conceptions underlying practices, with their own personal/professional narrative of the self. These results allow us to understand how significant changes in teachers' lifelong learning cycle can be rooted in specific networked learning practices. In this sense, connections with specific resources; "learning rituals", and educational values lead to shape symbolic constellations as part of professional identity on complex, open networks. This will surely configure a new frontier for TPD, where professional learning environments will be supported by complex processes of networked learning.